2012
DOI: 10.1037/a0028389
|View full text |Cite
|
Sign up to set email alerts
|

The effects of feedback during exploratory mathematics problem solving: Prior knowledge matters.

Abstract: Providing exploratory activities prior to explicit instruction can facilitate learning. However, the level of guidance provided during the exploration has largely gone unstudied. In this study, we examined the effects of 1 form of guidance, feedback, during exploratory mathematics problem solving for children with varying levels of prior domain knowledge. In 2 experiments, 2nd- and 3rd-grade children solved 12 novel mathematical equivalence problems and then received brief conceptual instruction. After solving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
61
2
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(74 citation statements)
references
References 79 publications
(161 reference statements)
10
61
2
1
Order By: Relevance
“…In problem solving, prior knowledge about related strategies enhances the efficiency of problem exploration, according to Fyfe et al (2012). Another group of researchers forge a link between employees' levels and the types of knowledge required.…”
Section: H18: Creativity Positively Impacts Knowledge Applicationmentioning
confidence: 97%
“…In problem solving, prior knowledge about related strategies enhances the efficiency of problem exploration, according to Fyfe et al (2012). Another group of researchers forge a link between employees' levels and the types of knowledge required.…”
Section: H18: Creativity Positively Impacts Knowledge Applicationmentioning
confidence: 97%
“…We designed the transfer items to be more structurally complex than the instruction items. We based this on previous studies of math equivalence that had used transfer tests with similar-aged children (e.g., Alibali, 1999;Fyfe, Rittle-Johnson, & DeCaro, 2012;Matthews & Rittle-Johnson, 2009;Perry, 1991). Problems differed from instructional problems in terms of addends on the left side (e.g., three instead of two), the position of the blank (a þ b þ c ¼ __ þ c), and the presence/absence of a repeated addend (a þ b þ c ¼ d þ __).…”
Section: Transfer Test Phasementioning
confidence: 99%
“…However, with additional developing knowledge of the domain, feedback delivered immediately after every problem solving step could become disruptive to learning because students are required to mentally process new (and extraneous) information rather than continuing to the next step. Learners in more advanced stages of learning may have already developed problem-solving schemas; thus, presenting immediate feedback after each problem solving step could unnecessarily disrupt their problem-solving process, creating extraneous processing demands and hindering learning (Fyfe, Rittle-Johnson, & DeCaro, 2012;Kalyuga, 2007;Kelley & McLaughlin, 2012;Kester & Kirschner, 2009). This study found no significant difference between the TFS-P and SFS conditions, indicating that in the examined engineering problem solving instruction, the feedback after each problem step did not significantly disrupt learning for the novice students.…”
Section: Discussionmentioning
confidence: 99%